Researchers’ Reading Log – Two Books About Cooperation - Jacobs, George M. (Autonomy and Responsibility Journal of Educational Sciences, 2024)
The Power of Us - Review Van Bavel, J. J. & Packer, D. J. (2021). The power of us: Harnessing our shared identities to improve performance, increase cooperation, and promote social harmony. Hachette Book Group Econarrative - Review Stibbe, A. (2024) Econarrative: Ethics, ecology and the search for new narratives to live by Bloomsbury.